Pelaksanaan Perjanjian Penyedia Jasa Satuan Keamanan (SATPAM) Antara Bank Danamon Indonesia Dan PT. Bravo Satria Perkasa - Farah Savira; Lalu Hadi Adha; Wiwiek Wahyuningsih (Private Law, 2023)
This study aims to find out the implementation of the security guard service provider agreement at PT. Bank Danamon Indonesia and PT. Bravo Satria Perkasa and to find out the obstacles encountered in implementing the security service provider agreement at PT. Bank Danamon Indonesia and PT. Bravo Satria Perkasa. The method used is an empirical normative legal research method. The results of the study can be concluded that (1) The implementation and legal protection for contract workers at PT Bravo Satria Perkasa are in accordance with the PKWT Work Agreement and the Labor Law (2) Obstacles that arise in the implementation of work agreements for a certain time at PT Bravo Satria Perkasa in the form of contract changes every 5 years for workers (security guards) so that PT Danamon Indonesia needs to conduct training or retraining for new workers (security guards) related to knowledge about banking and with the replacement of new security guards they cannot adjust to work rhythms, therefore need to be given periodic explanations in order to meet the disciplinary standards set by Bank Danamon.